2003
DOI: 10.1023/a:1022645116030
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Metastasis is the leading cause of death in patients with cervical cancer. In this report, we establish novel fluorescent HeLa tumor metastasis models to determine whether HeLa transfected with the enhanced red fluorescent protein (DsRed2) gene in vitro and xenotransplanted through subcutaneous, intraperitoneal, or intravenous route into SCID mice would permit the detection of tumor micro-metastasis in vivo. Our results showed that DsRed2 insertions did not interfere the tumorigenic properties of HeLa cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We first compared the expression of plakoglobin in weakly metastatic MCF7, nonmetastatic T47D, and highly metastatic HeLa, MDA-MB-436, and MDA-MB-231 cell lines [13-16,21-24]. Real-time PCR analysis showed significantly higher levels of plakoglobin in MCF7 and T47D breast cancer cells compared with HeLa, MDA-MB-231, or MDA-MB-426 ( P < 0.0001 for T47D cells and P < 0.005 for MCF7 cells compared with HeLa, MDA-MB-231, or MDA-436) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first compared the expression of plakoglobin in weakly metastatic MCF7, nonmetastatic T47D, and highly metastatic HeLa, MDA-MB-436, and MDA-MB-231 cell lines [13-16,21-24]. Real-time PCR analysis showed significantly higher levels of plakoglobin in MCF7 and T47D breast cancer cells compared with HeLa, MDA-MB-231, or MDA-MB-426 ( P < 0.0001 for T47D cells and P < 0.005 for MCF7 cells compared with HeLa, MDA-MB-231, or MDA-436) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have designed small ssRNA sequences of approximately 22 nucleotides in length that trigger gene silencing through specific cleavage and RNA degradation to target plakoglobin exclusively [11,12]. We compared the effects of reduced plakoglobin expression in weakly metastatic MCF7 and nonmetastatic T47D breast cancer cells on growth, adhesion, migration, and invasion in vitro [13-16]. In addition, we analyzed tumor growth and intravasation from the mouse mammary fat pad into the circulation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al reported a hierarchy of BCCs with the most immature subset (Oct4 hi /CD44 hi/med /CD24 -/+ ) demonstrating chemoresistance, dormancy, and stem cell properties [ 4 ]. Moreover, gene analysis revealed that these BCCs cell subtype (with CD44 + /CD24 − / claudin-low expression) also possessed higher flexibility that allowed them to change shape to pass through micro-barriers [ 4 , 5 , 91 ].…”
Section: Discussionmentioning
confidence: 99%